N‐Doped C@Zn3B2O6 as a Low Cost and Environmentally Friendly Anode Material for Na‐Ion Batteries: High Performance and New Reaction Mechanism - Wang, Sai; Zhang, Xin‐Bo (Advanced materials (Weinheim), 2019)
Na‐ion batteries (NIBs) are ideal candidates for solving the problem of large‐scale energy storage, due to the worldwide sodium resource, but the efforts in exploring and synthesizing low‐cost and eco‐friendly anode materials with convenient technologies and low‐cost raw materials are still insufficient. Herein, with the assistance of a simple calcination method and common raw materials, the environmentally friendly and nontoxic N‐doped C@Zn3B2O6 composite is directly synthesized and proved to be a potential anode material for NIBs. The composite demonstrates a high reversible charge capacity of 446.2 mAh g−1 and a safe and suitable average voltage of 0.69 V, together with application potential in full cells (discharge capacity of 98.4 mAh g−1 and long cycle performance of 300 cycles at 1000 mA g−1). In addition, the sodium‐ion storage mechanism of N‐doped C@Zn3B2O6 is subsequently studied through air‐insulated ex situ characterizations of X‐ray diffraction (XRD), X‐ray photoelectron spectroscopy (XPS), and Fourier‐transform infrared (FT‐IR) spectroscopy, and is found to be rather different from previous reports on borate anode materials for NIBs and lithium‐ion batteries. The reaction mechanism is deduced and proposed as: Zn3B2O6 + 6Na+ + 6e− ⇋ 3Zn + B2O3 ∙ 3Na2O, which indicates that the generated boracic phase is electrochemically active and participates in the later discharge/charge progress. N‐doped C@Zn3B2O6 (NC@ZBO) composite is chemically synthesized in a green manner through a simple method, and shows considerable sodium‐ion storage ability, including high reversible charge capacity (446.2 mAh g−1) and suitable average voltage (0.69 V), together with application potential in full cells (300 cycles). The sodium‐ion storage mechanism of Zn3B2O6 is also found rather different from relevant experiments on borates and deduced to be Zn3B2O6 + 6Na+ + 6e− ⇋ 3Zn + B2O3 · 3Na2O.